Effectofrosiglitazoneonserum IGF-I concentrations in uncontrolled acromegalic patients under conventional medical therapy: Results froma pilot phase 2 study - Bogazzi, F.; Rossi, G.; Lombardi, M.; Raggi, F.; Urbani, C.; Sardella, C.; Cosci, C.; Martino, E. (Journal of endocrinological investigation, 2011)
Objective : Current therapies for acromegaly are unsatisfactory for some patients. High-dose thiazolidinediones have been reported to reduce serum GH levels in animal models of acromegaly. The objective of the study was to evaluate the effect of increasing doses of rosiglitazone on serum GH and IGF-I concentrations in acromegalic patients. Design : Phase 2 clinical trial. Patients and methods : Five consecutive patients with active and uncontrolled acromegaly under conventional medical therapies were treated with increasing doses of rosiglitazone [4 mg/day every month, starting from 8 up to 20 mg/day] added to previous medical therapies for acromegaly. Results : Mean serum IGF-I concentrations decreased from 547±91 to 265±126 μg/l ( p <0,001) during rosiglitazone treatment: 4 patients had normal serum IGF-I concentrations, and a patient had lowered serum IGF-I values, although still abnormal, at the end of the study. On the contrary, serum GH concentrations did not significantly changed during rosiglitazone therapy as well as other pituitary hormones. No relevant side effects of rosiglitazone were observed during the study period. Quantitative real time PCR and Western blotting showed that rosiglitazone lowered GH-dependent hepatic generation of IGF-I in HepG2 cell line. Conclusions : Rosiglitazone reduces serum IGF-I concentrations in patients with uncontrolled acromegaly under conventional medical therapies, likely actingonthe GH-dependent hepatic synthesisof IGF-I. Large studies are necessary to confirm the role of rosiglitazone as an adjunctive therapy for uncontrolled acromegalic patients under conventional medical therapies.